Clinical Implications of Oscillatory Lung Function during Methacholine Bronchoprovocation Testing of Preschool Children. (27th June 2017) - Choi, Sun Hee; Sheen, Youn Ho; Kim, Mi Ae; Baek, Ji Hyeon; Baek, Hey Sung; Lee, Seung Jin; Yoon, Jung Won; Rha, Yeong Ho; Han, Man Yong
Abstract : Objective. To investigate the repeatability and safety of measuring impulse oscillation system (IOS) parameters and the point of wheezing during bronchoprovocation testing of preschool children. Methods. Two sets of methacholine challenge were conducted in 36 asthma children. The test was discontinued if there was a significant change in reactance (Xrs5) and resistance (Rrs5) at 5 Hz (Condition 1) or respiratory distress due to airway obstruction (Condition 2). The repeatability of PC80 _Xrs5, PC30 _Rrs5, and wheezing (PCw) was assessed. The changes in Z -scores and SD-indexes from prebaseline (before testing) to postbaseline (after bronchodilator) were determined. Results. For PC30 _Rrs5, PC80 _Xrs5, and PCw for subjects, PC80 _Xrs5 showed the highest repeatability. Fifteen of 70 tests met Condition 2 . The changes from pre- and postbaseline values varied significantly for Rrs5 and Xrs5. Excluding subjects with Z -scores higher than 2SD, we were able to detect 97.1% of bronchial hyperresponsiveness during methacholine challenge based on the change in Rrs5 or Xrs5. A change in IOS parameters was associated with wheezing at all frequencies. Conclusion . Xrs5 and Rrs5 have repeatability comparable with FEV1, and Xrs5 is more reliable than Rrs5. Clinicians can safely perform a challenge test by measuring the changes in Rrs5, Xrs5, and Z -scores from the prebaseline values.